DIGITAL INNOVATION WITH HUMAN-CENTERED VALUES: REFRAMING ENTREPRENEURSHIP FOR SOCIAL SUSTAINABILITY - Ryan Teo; Rachel Chan; Eva Janssen; Erni Nurhayani (Yayasan Adra Karima Hubbi, 2026)
In response to growing global challenges such as inequality, climate change, and resource scarcity, the role of digital innovation in entrepreneurship has gained prominence. Traditional models of entrepreneurship often prioritize profit maximization, while the increasing need for sustainable development calls for a shift towards more human-centered approaches. This research explores the intersection of digital innovation and human-centered values within entrepreneurship, focusing on how these innovations can contribute to social sustainability. The study aims to examine how entrepreneurs are integrating digital technologies with social values to create businesses that not only generate economic returns but also address societal issues. A mixed-methods approach was employed, combining qualitative interviews with entrepreneurs and quantitative data on business performance and social impact. The findings reveal that businesses incorporating human-centered values into their digital innovations saw enhanced market reach, operational efficiency, and social impact. This research concludes that reframing entrepreneurship to integrate social and environmental goals alongside economic objectives is critical for creating sustainable, inclusive business models. By emphasizing human-centered values, digital innovation can become a powerful driver for social sustainability.